Do Religiosity Moderate Tax Discrimination and Tax Information Technology on Tax Evasion? - Suyanto, Suyanto; Agustina, Ema; Putri, Fuadhillah Kirana (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This study examines the influence of tax discrimination and information technology on tax evasion, with religiosity as a moderating variable. The increasing number of tax evasion cases in Indonesia highlights the need to explore factors that drive non-compliance among taxpayers. Many individuals remain reluctant to fulfil their tax obligations due to concerns about unfair treatment by tax authorities and mismanagement of tax revenues. This study employs a quantitative research design with primary data collected through a structured questionnaire distributed to 132 MSME taxpayers in the Special Region of Yogyakarta using snowball sampling. The data were analyzed using multiple linear regression and moderated regression analysis (MRA) with SPSS 26. The findings indicate that tax discrimination significantly increases tax evasion, as perceived unfairness in tax policies reduces taxpayers' willingness to comply. Conversely, tax information technology negatively affects tax evasion, as digital innovations enhance transparency, monitoring, and enforcement, making non-compliance more difficult. Religiosity is found to play a moderating role in both relationships. It weakens the positive impact of tax discrimination on tax evasion, suggesting that individuals with strong religious values are less likely to justify evasion, even when they perceive discrimination. Similarly, religiosity mitigates the negative effect of tax information technology on tax evasion, implying that religious taxpayers are more likely to comply when they perceive the tax system as fair and aligned with ethical principles. These findings emphasize the need for policymakers and tax authorities to ensure fair tax administration and strengthen digital tax systems while also considering ethical and religious values to promote voluntary compliance. Integrating technological advancements with moral reinforcement strategies may serve as a more comprehensive approach to reducing tax evasion and enhancing tax compliance in Indonesia.